2009
DOI: 10.5216/rpt.v38i2.6625
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos Anatomopatológicos E Bioquímicos Da Coccidiose Hepática Em Coelhos

Abstract: Aspectos patológicos e bioquímicos foram avaliados por 28 dias em coelhos adultos, machos, raça Nova Zelândia, brancos, infectados experimentalmente com oocistos esporulados de Eimeria stiedae. Foram usados 50 animais distribuídos em dois grupos: grupo A infectado com 1x10 4 oocistos esporulados de E. stiedae e grupo B inoculado com água destilada. Os exames bioquímicos evidenciaram alterações nos níveis de bilirrubina, aspartato-amino-transferase, alanina-aminotransferase, fosfatase alcalina e gama-glutamil-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…From a biochemical point of view, the animals in the present experiment presented elevated concentrations of bilirubin, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and gamma-glutamyl transferase (FREITAS et al, 2009). In the same study, these authors observed ascites, hepatomegaly associated with congestion and fibrosis, thickening of the bladder wall and bile retention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From a biochemical point of view, the animals in the present experiment presented elevated concentrations of bilirubin, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase and gamma-glutamyl transferase (FREITAS et al, 2009). In the same study, these authors observed ascites, hepatomegaly associated with congestion and fibrosis, thickening of the bladder wall and bile retention.…”
Section: Resultsmentioning
confidence: 99%
“…The condition may progress to death, which is attributed to the hepatic lesions that are also associated with the infection (GOMEZ-BAUTISTA et al, 1986). In the study conducted by Freitas et al (2009), infection due to E. stiedai caused ascites, hepatomegaly associated with congestion and fibrosis, thickening of the bladder wall and retention of bile.…”
Section: Introductionmentioning
confidence: 99%
“…Uma exceção foi o Caprino 7, que apresentou aumento significativo, porém, isolado, na concentração de ALP aos 29 dias de ingestão das sementes. Acreditamos que esta alteração tenha ocorrido em virtude do desafio da eimeriose, confirmado através de exame parasitológico de fezes, e não teve nenhuma relação com a ingestão das sementes, já que segundo Freitas et al (2009), infecções por espécies de Eimeria podem levar a aumento nos níveis de ALP e outras enzimas.…”
Section: Discussionunclassified